Respuesta :

Answer:

(g+f)(x)=(2^x+x-3)^(1/2)

Step-by-step explanation:

Given  

f(x)= 2^(x/2)

And

g(x)= √(x-3)

We have to find (g+f)(x)

In order to find (g+f)(x), both the functions are added and simplified.

So,

(g+f)(x)= √(x-3)+2^(x/2)  

The power x/2 can be written as a product of x*(1/2)

(g+f)(x)= √(x-3)+(2)^(1/2*x)

We also know that square root dissolves into power ½

(g+f)(x)=(x-3)^(1/2)+(2)^(1/2*x)

We can see that power ½ is common in both functions so taking it out

(g+f)(x)=(x-3+2^x)^(1/2)

Arranging the terms

(g+f)(x)=(2^x+x-3)^(1/2)  ..